PERANAN APARATUR PEMERINTAHDALAM PELAYANAN PUBLIK DI PUSKESMAS BAHU KOTA MANADO - Masloman, Christy (Sam Ratulangi University, 2017)
Abstract: The purpose of this research is to know the role of government apparatus in public service at Puskesmas BahuManado City. This type of research uses descriptive qualitative analysis technique, that is to know the relationshipbetween government apparatus variable in Puskesmas Bahu Manado City with the quality of public service. Thisresearch is kuanlitatif because it uses data that require calculation and use kuanlitatif analysis to give description aboutdata that have been obtained so that more clearly understood. In this research there are variable x, that is professionalismservice officer Puskesmas Bahu. Level accuracy of data and information obtained, the authors assigned the respondentsby purposive as many as 30 patients or families of patients who seek treatment at the Puskesmas Bahu Manado City.Referring to the findings in this study, it is necessary to put forward some suggestions as follows: To optimize theperformance of health services related to the implementation of the dimensions of public service quality, it isrecommended that the management of puskesmas, especially Manado City Health Office encourage efforts to improveand improve service performance health through quality improvement and number of health workers, medical equipmentand other supporting facilities.Keywords: Public role and service